2006
DOI: 10.1016/j.clpt.2006.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative effect of CYP2D6 genotype and inhibitors on tamoxifen metabolism: Implication for optimization of breast cancer treatment

Abstract: CYP2D6 genotype and concomitant potent CYP2D6 inhibitors are highly associated with endoxifen plasma concentration and may have an impact on the response to tamoxifen therapy. These iterative approaches may be valuable in the study of other complex genotype-phenotype relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
387
3
13

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(418 citation statements)
references
References 29 publications
14
387
3
13
Order By: Relevance
“…The blood concentrations of tamoxifen's most potent and abundant metabolite, endoxifen, have been shown to correlate significantly with the CYP2D6 phenotype. 21,29 Furthermore, Goetz et al 22 reported that patients with impaired CYP2D6 metabolism have nearly a twofold higher risk of BC recurrence when treated with tamoxifen in the adjuvant setting. Moreover, the subjects' phenotype appeared to result from the combination of the genotype and drugs (or nutrients) that may interact with CYP450, in particular antidepressants and CYP2D6, as reported by Goetz et al, 31 with a fourfold increase of BC relapse in PM subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood concentrations of tamoxifen's most potent and abundant metabolite, endoxifen, have been shown to correlate significantly with the CYP2D6 phenotype. 21,29 Furthermore, Goetz et al 22 reported that patients with impaired CYP2D6 metabolism have nearly a twofold higher risk of BC recurrence when treated with tamoxifen in the adjuvant setting. Moreover, the subjects' phenotype appeared to result from the combination of the genotype and drugs (or nutrients) that may interact with CYP450, in particular antidepressants and CYP2D6, as reported by Goetz et al, 31 with a fourfold increase of BC relapse in PM subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Genotypically, PM patients or patients receiving CYP2D6-inhibiting drugs have reduced plasma concentrations of endoxifen. 14,15,21 At the clinical level, PM subjects with BC on adjuvant tamoxifen tend to have a higher risk of relapse. 22,23 This worse clinical outcome has been associated with a decreased prevalence of hot flashes, a putative marker of tamoxifen activity.…”
Section: Introductionmentioning
confidence: 99%
“…For that drugegene pair, multiple studies have demonstrated that patients with poor metabolizer genotypes are more likely to have worse outcomes. This is due to suboptimal conversion (primarily via CYP2D6) of tamoxifen into the more potent, active antiestrogenic metabolites, endoxifen and 4-hydroxytamoxifen (Higgins and Stearns, 2010), a relationship which is supported by pharmacokinetic data showing that patients with these genotypes have lower levels of endoxifen (Borges et al, 2006). In one study, 206 tamoxifen-treated patients receiving the drug in the adjuvant setting were compared based upon genotype groups (Schroth et al, 2007) for disease-related outcomes.…”
Section: Fcgriia Fcgriiiamentioning
confidence: 99%
“…These metabolites compete with estrogen for the ligand-binding domain (LBD) of the ER, blocking the potential for estrogen stimulation and preventing conformational changes in the receptor critical for the association of cofactors and the transcription of estrogen-responsive genes [43]. Variations in this isoform, whether genetic (e.g., wild-type variant CYP2D61*) or as a result of inhibition by selective serotonin reuptake inhibitors (e.g., fluoxetine and paroxetine) [44], may alter the metabolism of tamoxifen, blunting its antiestrogenic activity [45].…”
Section: Endocrine Resistance In Breast Cancermentioning
confidence: 99%